(untitled) (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2013)
This paper studies the principle of equal treatment of aliens and nationals, speciallywith regard to the recognition or exercise of rights. The main part of the analysis focuses on Spanish Law and the way in which it reflects the aforementioned principle both in the Spanish Constitution and in legislation. Finally, from a legal pointof view, the paper critizises the view that defends the substitution of the idea of nationality by the concept of citizenship in the regulation of inmigrant aliens rights.